Pengaruh Perbandingan Resin Dan Katalis Terhadap Kekuatan Tarik Komposit Fiberglass-Polyester Untuk Bahan Pembuatan Kapal - Alamsyah Alamsyah; Taufik Hidayat; Arif Nur Iskandar (Departemen Teknik Kelautan Universitas Hasanuddin, 2020)
The use of fiberglass-based composites is often found in shipbuilding. However, the use of composites in the shipbuilding process does not yet have clear and standard quality standards regarding the ratio between the amount of resin and catalyst used. Meanwhile, the amount of use of resin and atalyst has an influence on the strength of the fiber-reinforced composite. This study aims to determine the effect of the amount of catalyst mixed into the resin on the tensile strength of fiberglass-polyester composites. The method used in this study is an xperimental method that uses a tensile testing machine by varying the amount of catalyst in the resin from 0.5% to 2%. In this study, the results showed that composites with a catalyst amount of 0.5% had a tensile strength value of 4.85 kgf/mm2, elongation of 2.43% and elastic modulus of 2.26 kgf/mm2. Composites with a catalyst amount of 1% had a tensile strength value of 5.02 kgf/mm2, longation of 1.71% and elastic modulus of 2.96 kgf/mm2. Composites with a catalyst amount of 1.5% had a tensile strength value of 5.49 kgf/mm2, longation of 1.97% and elastic modulus of 3.07 kgf/mm2. Composites with a catalyst amount of 2% had a tensile strength value of 4.97 kgf/mm2, longation of 1.62% and elastic modulus of 3.11 kgf/mm2. The tensile strength of fiberglass-polyester composites has increased in the amount of catalyst 0.5 to 1.5% and has decreased in the amount of catalyst 2%. The highest value of tensile strength is in composites with a composition of 100% resin and 1.5% catalyst.